The poetry and poetics of Gerald Vizenor - Madsen, Deborah L. (University of New Mexico Press, 2012)
"The first book devoted exclusively to the poetry and literary aesthetics of one of Native America's most accomplished writers, this collection of essays brings together detailed critical analyses of single texts and individual poetry collections from diverse theoretical perspectives, along with comparative discussions of Vizenor's related works"--Provided by publisher.